Acceptability and usability of Drugs4dent®, a dental medicines decision tool – a pilot study - Leanne Teoh; Ruby Biezen; Marietta Taylor; Richard O. Sinnott; Michael J. McCullough (BMC Oral Health)
Abstract Background While drugs have a limited role in the management of dental presentations, Australian dentists have high rates of inappropriate prescribing of antibiotics. There is also a lack of relevant drug resources for dentists in Australia. Our team developed Drugs4dent®, a medicines decision support tool, that provides dentists with relevant drug knowledge, assists with appropriate prescribing and provides safety checks to reduce prescribing errors. The aim of this pilot study was to improve Drugs4dent® with focus groups of dentists, and assess the acceptability, usability, and user experience, of Drugs4dent®. Methods Focus groups of ten dentists were established to inform the improvement of Drugs4dent®. Acceptability and usability testing of Drugs4dent® was then undertaken with a further ten dentists using interviews and a survey. The survey was based on the Framework for Acceptability and System Usability Scale. Inductive thematic analysis was undertaken using Nvivo for the focus groups and interviews, and descriptive statistics for analysis of survey results. Results Dentists from the focus group and interviews found the content of Drugs4dent® acceptable and useful for dentistry, recognising that similar drug information is currently not available. The majority agreed that Drugs4dent® would improve their ability to prescribe according to guidance. Participants reported Drugs4dent® was intuitive, and information was easy to locate. Most dentists preferred Drugs4dent® integrated with their dental practice software. In the absence of this functionality, they preferred Drugs4dent® as a standalone resource, without needing to input patient data. Drugs4dent® was subsequently commercialised with MIMS Australia, to create the decision support tool: MIMS Drugs4dent®. Conclusions Drugs4dent® is the first dental medicines decision tool in Australia. The high acceptability and usability of the tool, and subsequent commercialisation indicates that MIMS Drugs4dent® has substantial promise for the future, and can transform access to relevant drug information for Australian dentists.